Toward the construction of parameter‐free doubly hybrid density functionals. Issue 10 (17th December 2014) - Su, Neil Qiang; Xu, Xin
<x xml:space="preserve">Abstract</x> Doubly hybrid (DH) functionals present a new class of density functionals, which enfold the nonlocal orbital‐dependent components not only in the exchange part but also in the correlation part. Different types of DH functionals have been proposed according to different philosophies. DH functionals are shown to better fulfill certain physical conditions such as the linearity condition for fractional charges than other conventional functionals, which accounts for the generally improved performances of DH functionals in the description of thermochemistry and thermochemical kinetics for the main group chemistry. Efforts shall be made toward the construction of parameter‐free DH functionals and the proper description of the dissociation limit with strong static correlation. The latter is related to the fractional spin errors, the reduction of which is important for secure applications in transition metal chemistry. © 2014 Wiley Periodicals, Inc.